GENETIC DIVERSITY OF LIMA BEAN (PHASEOLUS LUNATUS L.) FROM TIMOR ISLAND BASED ON MOLECULAR MARKER INTER-SIMPLE SEQUENCE REPEATS (ISSR) - Emilia Juliyanti Bria; Polikarpia Wilhelmina Bani (PTTI, 2021)
Lima bean (Phaseolus lunatus L.) is one of the important legume vegetables in Indonesia. However, genetic information for these plants is still minimalized, especially on Timor Island. This study aims to analyze the genetic diversity of lima beans from Timor Island based on ISSR molecular markers. A total of 4 accessions of lima beans were analyzed using 3 ISSR primers to produce 15 polymorphic bands with an average of 68.18% polymorphism. The cluster analysis results use the Unweighted Pair Group Methods using Arithmetic averages (UPGMA) method to create a dendrogram that produces two main clusters. There were plain seed and pattern seed group with a similarity coefficient of 0.52. These results indicated that the genetic variation of the lima beans from Timor Island was high. Moreover, the result provides a sutable method for evaluating the genetic diversity of lima beans using the ISSR marker and important information of future lima bean breeding programs.